Isolation and Characterization of Rhizosphere Bacteria and their Effect on Germination of Rice Seeds and Growth of Seedlings - Nasrin, Shamima; Rahman, MA (Journal of Bio-Science, 2009)
Rhizosphere bacteria were isolated from root zones from rice fields. These were cultured in laboratory conditions and investigated the effects on germination and growth of rice seedlings. They inhabit around the roots and live on root exude and benefit the plants by altering the solubility and availability of mineral nutrients and protecting the roots from invasion of pathogens by creating an antibiotic barrier around the root. It has been found that rhizosphere bacteria have no effect on germination of rice seeds. Both the rhizosphere bacteria and the Agrobacterium have been found to produce better growth of rice seedlings in pot cultures but later is less effective than the former. Rhizosphere bacteria are mixtures of many e.g. Actimomyces, Proteobacteria, Pseudomonas etc. but Agrobacterium sp is single. Key words: Rhizosphere, Bacteria, Symbiosis, Soil microflora, Non-leguminous plants. doi: 10.3329/jbs.v15i0.2206 J. bio-sci. 15: 77-82, 2007